Sistem Informasi Program Kerja ASLAB Berbasis Web (Studi Kasus GI-BEI PSDKU Polinema di Kota Kediri) - Yanda Muhammad Naufall. A (Jurnal Informatika dan Multimedia, 2022)
Data processing of work programs at the Indonesian Stock Exchange Investment Gallery Laboratory Assistant (ASLAB GI-BEI) belonging to the accounting department at the PSDKU Polinema campus in Kediri City is still running with a manual system. This work program data processing still uses paper to record the formation of the committee, attendance data and meeting minutes. Then for the work program data processing using the Microsoft Excel application to create reports. Work program data will not be effective if data recording is done manually. Besides being difficult, recording data manually using paper is very risky, such as damage and loss of recording books. Meanwhile, recording data using the Microsoft Excel application is also less efficient and effective, which allows redundancy and errors in writing data. Therefore, we need a website-based application that can manage data recording of work program activities with the aim of making it easier for ASLAB GI-BEI to process data on work program activities online. This work program information system is made in the Laravel Framework with PHP programming language and MySQL database. This activity information system has 3 users, namely Members, Chairpersons, and Supervisors. The application features consist of user management, application management, work program management, meeting management, committee management, and LPJ management.